Validação de método analítico e de extração do malation em água e solo após nebulização de combate ao Aedes aegypti - Coleone, Ana Carla [UNESP]; da Silva, Flavio Soares; Machado, Angela Aparecida [UNESP]; Neto, Joaquim Gonçalves Machado [UNESP]; Paganini, Wanderley da Silva (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2017)
The Aedes aegypti mosquito is a vector of diseases such as dengue, yellow fever, chikungunya and zika, which has great relevance to public health. In urban areas, ultra-low volume (ULV) malathion fogging is used for the control of adult mosquitoes. Spraying with the insecticide can contaminate soil and water. The goal of this study was to adjust and validate an analytical method for the determination of malathion in high-performance liquid chromatography (HPLC) and determine the pesticide extraction method of water and soil matrices. The mobile phase used an isocratic mixture of acetonitrile and water (68:32), at a flow rate of 1 mL min-1, an injection volume of 20 μL, and a UV at 210 nm. After fortification, the analyte was extracted with acetonitrile (ACN) by mechanical agitation of the soil samples, and by evaporation of the water samples, pre-concentrated, re-dissolved in ACN, and the recovery was calculated. The method is simple, specific and suitable for analysis of malathion with linearity between concentrations of 0.050 and 1.00 μg mL-1 (R2 = 0.999) and detection limits of 0,017 μg mL-1 and quantification of 0.051 μg mL-1. The average recovery of malathion from water was 97%, and from soil, 96%, being the method exact and precise (coefficient of variation <8.8%). The set method can be safely used for the quantification of the insecticide in water and soil matrices.
Analytical method of validation and extraction of malathion in water and soil after fogging against Aedes aegypti
Keywords: Insecticide; Liquid chromatography; Public health